(untitled) (Journal of Asian Development Studies, 2025)
This study examines the mechanisms of algorithmic governmentality, state-controlled consciousness, and systemic conditioning in Aldous Huxley’s Brave New World, exploring how governance in the novel operates through predictive control, technological intervention, and psychological manipulation. Drawing on the theoretical framework of algorithmic governmentality (Rouvroy & Berns, 2013), the research analyzes the techno-authoritarian structures that regulate human behavior, suppress individual consciousness, and engineer societal compliance through systemic conditioning. In the novel, genetic standardization, hypnopaedic indoctrination, pharmacological pacification, and data-driven surveillance function as tools of state-controlled consciousness, systematically shaping perception, emotions, and decision making. This study situates Brave New World within contemporary discussions on algorithmic control, bio-political regulation, and digital authoritarianism, demonstrating its prescient relevance to modern-day concerns surrounding AI-driven governance, predictive policing, and data capitalism. Ultimately, this research highlights Huxley’s work as a cautionary critique of a future where systemic conditioning and algorithmic governance converge to redefine human autonomy, free will, and ideological conformity.